Analysis of Coal Feeder Motor Performance Under the Influence of Frequency Fluctuations at PLTU Pangkalan Susu - Hafist Aufar; Haris Gunawan; Siti Anisah (Sean Institute, 2025)
The coal feeder motor is a three-phase induction motor whose speed is regulated by the Variable Speed Drive (VSD). The coal feeder motor functions as a medium for distributing coal fuel to the combustion chamber in the boiler which aims for the combustion process in heating water on the pipe wall (wall tube) which will be used as steam to drive the turbine. Before supplying coal, first pay attention to the amount of coal entering the coal feeder, because it will affect the coal flow and motor performance. The more coal that enters the coal feeder, the greater the coal flow, just as the high speed of the motor will increase the flow of coal entering the furnace. From the research results, the calculation of the change in motor speed to the torque of the coal feeder motor at a speed of 115.2 rpm obtained a torque of 7.88 Nm, at a speed of 144 rpm obtained a torque of 6.68 Nm, at a speed of 230.4 rpm obtained a torque of 5.33 Nm and at a speed of 288 rpm obtained a torque of 4.48 Nm%. at a speed of 115.2 rpm an efficiency of 31.05% was obtained, at a speed of 144 rpm an efficiency of 29.55% was obtained.